Ab initio modeling of H2S dissociative chemisorption on Ag(100). Issue 31 (28th July 2022) - Ramothe, Vivien; Charlet, Laurent; Gilbert, Benjamin; Simonnin, Pauline; Sassi, Michel; Rosso, Kevin M.
Abstract : Natural sulfidation of silver nanomaterials can passivate the surface, while preserving desirable optical and electrical properties, which is beneficial for limiting Ag + release and cytotoxicity. Abstract : Natural sulfidation of silver nanomaterials can passivate the surface, while preserving desirable optical and electrical properties, which is beneficial for limiting Ag + release and cytotoxicity. But little is known at the atomic scale about silver sulfidation mechanisms, particularly on different crystallographic terminations. Using density functional theory (DFT) calculations, we examined the process of H2 S sorption and reaction on Ag(100) surfaces relevant to Ag nanowires (AgNWs). DFT energy minimizations predict a strong dissociative chemisorption of H2 S on the surface yielding co-adsorbed sulfide and hydrogen atoms in specific surface sites. However, nudged elastic band (NEB) calculations suggest relatively large activation energies for both the first and second dissociation steps, due in part to overcoming the energy to cleave the S–H bond and attendant site migration from an on-top Ag site position to a hollow site position of the bound S atom. The large barriers associated with the dissociative chemisorption reaction for gas-phase H2 S points to the importance of including thermochemical contributions and the influence of other components in more complex environmental media such as air or water to help complete the mechanistic picture of silver sulfidation and passivation for realistic systems.